Alphaworld: mighty mountains - Porter, Anna (Oxford University Press Melbourne, 2004)
"Mighty Mountains" is often a children's book that explores the beauty and majesty of mountains through vivid illustrations and engaging storytelling. The narrative typically highlights the wonders of nature, discussing the various ecosystems found in mountainous regions, the challenges of climbing, and the diverse wildlife that inhabits these areas. It may also touch on themes of adventure, exploration, and respect for nature, encouraging young readers to appreciate the great outdoors and understand the importance of preserving natural environments. The book aims to inspire curiosity about the world and foster a sense of adventure in its readers